Directive Speech Acts in Ariana Grande’s ‘Eternal Sunshine’ Interview with Zach Sang - Hidayati, Suci; Afriana (IKIP Siliwangi, 2025)
This study aims to analyze the use of directive speech acts in Ariana Grande’s Eternal Sunshine interview with Zach Sang, focusing on how commands, orders, requests, and suggestions shape conversational dynamics. Using George Yule’s (1996) classification as the theory, this research examines how language functions to influence and guide behavior in a media setting. The data source is the publicly available interview, and the research employs a qualitative descriptive design to systematically identify directive speech acts. Data was collected through observational method with non-participatory technique, and analyzed using the pragmatic identity method with contextual analysis technique, based on Sudaryanto (2015). Results show that requests, with 20 instances, were the most common directive, suggesting a preference for politeness. Commands followed with 16 instance, and suggestions appeared 15 times, indicating subtle influence, while orders were least frequent with 9 instances, highlighting sparing use of direct authority. These findings underscore how directive speech acts contribute to interaction flow and social dynamics in high-profile media contexts.